Parameters of a runaway electron avalanche - Oreshkin E. V. Evgeny Vladimirovich; Barengolts S. A. Sergey Aleksandrovich; Oreshkin V. I. Vladimir Ivanovich; Mesyats G. A. Gennady Andreyevich (2017, 2017)
Title screen